101 Things to Know and Do to Clean Up the Air - Puffin Books (Bharat Puffin Random House Bharat, 2019)
None of us can live without air to breathe. But our factories and cars are sending toxic chemicals into the air, making it difficult to stay healthy. It is also causing our planet to warm up very fast, which is bad for all living things. This book contains important information, helpful tips and stories of people who have found ways to clean up the air around us. There are also lots of fun activities and do-it-yourself projects for you to try at home.
Keywords: Global Issues -- Global Issues; Sustainels Practices -- Sustainels Practices